PENGEMBANGAN KEMASAN AYAM GEYBOK JARWO SEBAGAI UPAYA PENINGKATAN DAYA SAING PRODUK UMKM LOKAL - Septihani Michella Wijaya; Chiara Rizka Yukianti; frangky selamat; Chairy (Jurnal Bakti Masyarakat Indonesia, 2022)
The UMKM partners are Ayam Geybok Bang Jarwo, Tanjung Gedong branch, which provides chicken with a special sauce. This partner has branches in Tanjung Duren and Poris. The packaging for Ayam Geybok Bang Jarwo is currently in the development stage in stages so that it can advance its business and increase sales. One of the challenges faced by the UMKM Ayam Geybok Bang Jarwo is the product packaging which is still not suitable so it makes the food smell bad due to spilled oil when it is packaged. This, of course, makes the Bang Jarwo Geybok Chicken inferior to its competitors who already use better packaging. Partners want to learn how to develop good packaging and will make consumers interested in buying Ayam Geybok Bang Jarwo food. With the development of this packaging, partners want to study the development of packaging that will be an attraction for consumers but still maintain and not change the quality of the food. Consumers are very concerned about visualization and color, as well as the shape of the packaging, so it needs to be made attractive. However, the partners' lack of understanding of packaging development will become an obstacle for Ayam Geybok Bang Jarwo. This PKM helps partners focus on a hygienic and safe packaging process up to the consumer. The method used is by interviewing about the design of the current packaging, how to market and sell the product, the target market of the Ayam Geybok Bang Jarwo partners, the sales they get, and the partners of the Ayam Geybok Bang Jarwo Tanjung Duren and Poris branches. From the results of the interviews, it is known that partners have made digital sales through online food delivery. The result of this PKM activity is to make packaging for partners. ABSTRAK: Mitra UMKM adalah Ayam Geybok Bang Jarwo cabang Tanjung Gedong yang menyediakan ayam dengan sambel khas. Mitra ini memiliki cabang cabang di Tanjung Duren dan Poris. Kemasan Ayam Geybok Bang Jarwo saat ini sedang pada tahap pengembangan secara bertahap sehingga dapat memajukan bisnisnya dan meningkatkan penjualan. Salah satu tantangan yang dihadapi oleh UMKM Ayam Geybok Bang Jarwo adalah kemasan produknya yang masih belum sesuai, sehingga membuat makanan menjadi bau dikarenakan minyak yang tumpah pada saat di kemas. Hal ini tentu saja membuat Ayam Geybok Bang Jarwo kalah dengan pesaingnya yang sudah menggunakan kemasan yang lebih baik. Mitra ingin mempelajari cara pengembangan kemasan yang baik dan akan membuat konsumen berminat untuk membeli makanan Ayam Geybok Bang Jarwo. Dengan adanya pengembangan kemasan ini mitra ingin mempelajari pengembangan kemasan yang akan menjadi daya tarik bagi konsumen tetapi tetap menjaga serta tidak mengubah kualitas dari makanan. Konsumen sangat memperhatikan visualisasi dan warna, serta bentuk dari kemasan, sehingga perlu dibuat menarik. Namun, kurangnya pemahaman mitra terhadap pengembangan kemasan akan menjadi penghambat bagi Ayam Geybok Bang Jarwo PKM ini membantu mitra fokus pada proses pengemasan yang higenis dan aman sampai kepada konmen. Metoda yang dipakai adalah dengan wawancara tentang desain pada kemasan saat ini, cara memasarkan dan menjual produk, target pasar dari mitra Ayam Geybok Bang Jarwo, penjualan yang didapat, serta mitra Ayam Geybok Bang Jarwo cabang Tanjung Duren dan Poris. Dari hasil wawancara, diketahui bahwa mitra sudah melakukan penjualan secara digital melalui online food delivery.  Hasil dari kegiatan PKM ini adalah membuat kemasan untuk mitra